2016
DOI: 10.1021/acsami.6b06403
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Functionalized Silk Fibroin Films as a Platform To Guide Neuron-like Differentiation of Human Mesenchymal Stem Cells

Abstract: Surface interactions at the biomaterial-cellular interface determine the proliferation and differentiation of stem cells. Manipulating such interactions through the surface chemistry of scaffolds renders control over directed stem cell differentiation into the cell lineage of interest. This approach is of central importance for stem cell-based tissue engineering and regenerative therapy applications. In the present study, silk fibroin films (SFFs) decorated with integrin-binding laminin peptide motifs (YIGSR a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
64
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 67 publications
1
64
0
Order By: Relevance
“…The authors mentioned that NHS/EDC linker contributed to covalent attachment of COOH groups from sulfated glycosaminoglycan (GAG) with NH 2 groups of collagen in sulfated GAG–collagen matrices and provided considerable resistance of tissue scaffolds to enzymatic degradation . In another study, Manchineella et al showed that covalent modifications of silk fibroin (SF) films led to the increased proliferation of human multipotent mesenchymal stromal cells (hMSCs) relative to physical modification of SF films . These findings suggest that covalent modification would be appropriate approach for the long‐term culture experiments .…”
Section: Surface Modification Methodsmentioning
confidence: 99%
“…The authors mentioned that NHS/EDC linker contributed to covalent attachment of COOH groups from sulfated glycosaminoglycan (GAG) with NH 2 groups of collagen in sulfated GAG–collagen matrices and provided considerable resistance of tissue scaffolds to enzymatic degradation . In another study, Manchineella et al showed that covalent modifications of silk fibroin (SF) films led to the increased proliferation of human multipotent mesenchymal stromal cells (hMSCs) relative to physical modification of SF films . These findings suggest that covalent modification would be appropriate approach for the long‐term culture experiments .…”
Section: Surface Modification Methodsmentioning
confidence: 99%
“…26,3941 The presence of proteins on their surface can also modulate the interactions between the fibers and the cells, thereby affecting the differentiation of stem cells. 42,43 …”
Section: Introductionmentioning
confidence: 99%
“…Hence, designing 3D tissue engineering scaffolds with excellent biocompatibility and controllable biodegradability which can mimic the extracellular matrix and guide 3D tissue regeneration is highly required. Owing to the remarkable biocompatibility, silk fibroin (SF) has been widely used in biomaterials with a variety of forms, such as electrospun nanofibers, films, sponges, hydrogels, and scaffolds . Researchers recently used salt‐leaching method or organic solvent to prepare the water‐stable SF scaffolds for tissue engineering.…”
Section: Introductionmentioning
confidence: 99%